2016
DOI: 10.1002/pra2.2016.14505301071
|View full text |Cite
|
Sign up to set email alerts
|

Exploring linguistic diversity of MOOCS: Implications for international development

Abstract: Recent practical initiatives and academic research have signaled optimism for the use of Massive Open Online Courses (MOOCs) as an alternative model for education in the developing world. At the same time, anecdotal evidence and observation have pointed to a lack of courses offered in languages other than English as one potential challenge for global use of MOOCs. We present a first empirical attempt to characterize the linguistic diversity of MOOCs and understand the resulting implications for the use of MOOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
(27 reference statements)
0
6
0
4
Order By: Relevance
“…Besides the problem of network infrastructure discussed above, the English language proficiency is also an obstacle for non-native English speakers to adopt MOOCs. Indeed, it is found that over three-quarters of MOOCs available to learners worldwide are delivered in English (Stratton and Grace, 2016).This creates a barrier for learners who do not have proficiency in the English language (Agudo, 2019). Thus, to make MOOCs accessible to global learners, it is necessary to provide language translation services in MOOCs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the problem of network infrastructure discussed above, the English language proficiency is also an obstacle for non-native English speakers to adopt MOOCs. Indeed, it is found that over three-quarters of MOOCs available to learners worldwide are delivered in English (Stratton and Grace, 2016).This creates a barrier for learners who do not have proficiency in the English language (Agudo, 2019). Thus, to make MOOCs accessible to global learners, it is necessary to provide language translation services in MOOCs.…”
Section: Discussionmentioning
confidence: 99%
“…A language audit of MOOCs created between 2012 and 2015 estimated that 75% of MOOCs are produced in English; however, there is evidence of growing diversity (Stratton & Grace, 2016). MOOCs are now presented in Arabic (Adham & Lundqvist, 2015;Castillo et al, 2015), Chinese (Godwin-Jones, 2014;…”
Section: Participant Literaciesmentioning
confidence: 99%
“…It may be noted, with respect to the multilingual intention of the ILO MOOC, that the English language predominates in MOOCs generally. A study carried out in early 2016, examining the 4950 MOOCs listed in the Class Central database, showed that, although MOOCs in 17 languages could be identified, English language courses accounted for 76%, and five languages (English, Spanish, French, Chinese and Arabic) accounted for 95% [44]. As a comparison, the MOOC-list website offered MOOCs in 30 different languages in March 2017, but with English still predominant.…”
Section: 10mentioning
confidence: 99%